Open Source Software in Education - Lazić, Nikolaj; Klindžić, Jasmin; Banek Zorica, Mihaela (2011)
The paper presents different approaches to distribution of software: open VS closed source and free VS non-free. The differences are presented from the Croatian user perspective showing their positive and negative aspects. Additional analysis of curriculum regarding computer literacy is done in the light of decreased funding for schools by the Croatian Ministry of Science, Education and Sports. User survey was conducted at the Faculty of Humanities and Social Sciences, University of Zagreb to investigate usage of different software packages. Different approaches to computer literacy education are compared in the light of ongoing financial crisis in Croatia taking into account open and closed source software.
Projekt MZOS
Projekt MZOS
ENG